Analisis Resepsi Jurnalis Dalam Pemberitaan Infotainment - Bellica Cameysi; Aliasan; Jufrizal (CV. ITTC INDONESIA, 2024)
This research is entitled Analysis of Journalists' Receptions in Infotainment Reporting. Will discuss how journalists respond to infotainment reporting. Meanwhile, the data sources for this research are six (6) journalists, namely three journalists from Sumatra Express and three others from Radio Republik Indonesia (RRI). To collect data, the author used observation, documentation, literature study and interviews. After the data was collected, the data was analyzed using Stuart Hall's Encoding and Decoding Analysis Theory which classifies it into three categories, namely dominant position, negotiation and opposition. Furthermore, after being analyzed, the thesis will be presented in qualitative descriptive form. Meanwhile, findings in the field after the research found that there was one source who was in a dominant position, while in the opposition position there was one source, then as many as four sources were in a negotiating position.